Повреждения травматического и гипоксического генеза: общность патогенетических механизмов = Traumatic and hypoxic damages: common pathogenetic mechanisms - R. S. Vastyanov; A. N. Stoyanov; V. M. Demidov; D. V. Bylsky; S. A. Antonenko; N. V. Nescoromnaya; M. Yu. Sivolap; A. R. Pulyk (Kazimierz Wielki University, 2016)
Vastyanov R. S., Stoyanov A. N., Demidov V. M., Bylsky D. V., Antonenko S. A., Nescoromnaya N. V.,Sivolap M. Yu., Pulyk А. R. Повреждения травматического и гипоксического генеза: общность патогенетических механизмов = Traumatic and hypoxic damages: common pathogenetic mechanisms. Journal of Education, Health and Sport. 2016;6(9):285-304. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.61768 http://ojs.ukw.edu.pl/index.php/johs/article/view/3845       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 06.09.2016.     УДК 616-092;616-001;616.831-005.4+557.146.1   ПОВРЕЖДЕНИЯ ТРАВМАТИЧЕСКОГО И ГИПОКСИЧЕСКОГО ГЕНЕЗА: ОБЩНОСТЬ ПАТОГЕНЕТИЧЕСКИХ МЕХАНИЗМОВ   Р. С. Вастьянов, А. Н. Стоянов, В. М. Демидов, Д. В. Быльский, С. А. Антоненко, Н. В. Нескоромная, М. Ю. Сиволап, * А. Р. Пулык   Одесский национальный медицинский университет, Одесса * Ужгородский национальный университет, Ужгород  РезюмеИзученыбыли в сравнительном аспекте особенности процессов липопероксидации и антирадикальной защиты в крови животных с черепно-мозговой травмой (ЧМТ), ишемическим инсультом (ИИ) и острым панкреатитом (ОП). Дополнительно были исследованы концентрации фактора некроза опухоли-альфа, интерлейкина-1 и -6 и активность системы синтеза оксида азота в условиях использованных моделей травматического и гипоксического повреждения (ТГП). Показаны эффекты накопления в крови животных с ТГП промежуточных продуктов ПОЛ - МДА и ДК - и снижения активности антиоксидантных ферментов - каталазы, СОД и ГП, - что отмечалось в течение 14 дней наблюдения. Полученные данные свидетельствуют об усилении синтеза провоспалительных цитокинов и об активации нитратергической системы в модельных условиях. Применение ронколейкина в большинстве случаев способствует нормализации концентрации МДА и ДК, а также активности каталазы, СОД и ГП на 7 день после экспериментального воспроизведения ОП и на 14 день после моделирования ЧМТ и ИИ. Результаты работы свидетельствуют о формировании патологической дезинтеграции нервной и иммунной систем как о ведущем патофизиологическом механизме ТГП. Применение ронколейкина в модельных условиях выявило защитные эффекты, что является экспериментальным доказательством целесообразности клинического тестирования препарата у пациентов с травматическими и гипоксическими повреждениями органов. Ключевые слова:травматическое и гипоксическое повреждение, ронколейкин, патогенетические механизмы, патологическая дезинтеграция               TRAUMATIC AND HYPOXIC DAMAGES: COMMON PATHOGENETIC MECHANISMS  R. S. Vastyanov, A. N. Stoyanov, V. M. Demidov, D. V. Bylsky, S. A. Antonenko, N. V. Nescoromnaya, M. Yu.Sivolap, * А. R. Pulyk  Odessa National Medical University, Odessa; *UzhgorodNationalUniversity, Uzhgorod, SummaryLipid peroxidation and antiradical defense comparative peculiarities were studied in plasma of animals with brain trauma (BT), ischemic stroke (IS) and acute pancreatitis (AP). Tumor necrosis factor-alpha, interleukins-1 and -6 levels and nitric oxide synthesis enzyme activity were evaluated in the conditions of the traumatic and hypoxic damages (THD) models. Intermediate products of peroxidation - MDA and DK - levels accumulation as well as antioxidant enzymes - catalase, SOD and GP - activity decreasing in blood plasma of THD animals were evident throughout 14 days. The data obtained are in favour of proinflammatory cytokines synthesis enhancement and nitratergic system activation under the model conditions. Ronkoleukin administration in majority cases results in MDA and DK levels normalization together with catalase, SOD and GP activity increasing on the 7th day of the experimental trials in case of experimental AP and on the 14th day after BT and IS modelling. The results indicate both the nervous and immune systems pathological disintegration as a common leading THD pathophysiological mechanism. Ronkoleukin administration in these model conditions revealed protective effects that serve as an experimental background of its clinical testing reasonability in patients with inner organs traumatic and hypoxic damages. Keywords: traumatic and hypoxic damage, ronkoleukin, pathogenetic mechanisms, pathological desintegration,  РезюмеУРАЖЕННЯ ТРАВМАТИЧНОГО І ГИПОКСИЧНОГО ГЕНЕЗУ: СПІЛЬНІСТЬ ПАТОГЕНЕТИЧНИХ МЕХАНІЗМІВ. Вивчено було в порівняльному аспекті особливості процесів ліпопероксидації і антирадикального захисту в крові тварин з черепно-мозковою травмою (ЧМТ), ішемічним інсультом (ІІ) і гострим панкреатитом (ОП). Додатково були досліджені концентрації фактора некрозу пухлини-альфа, інтерлейкіну-1 і -6 та активність системи синтезу оксиду азоту в умовах використаних моделей травматичного і гіпоксичного ураження (ТГУ). Показано ефекти накопичення в крові тварин з ТГУ проміжних продуктів ПОЛ - МДА і ДК - і зниження активності антиоксидантних ферментів - каталази, СОД і ГП, - що відзначалося протягом 14 діб досліду.